Comprehensive evaluation method of groundwater environment in a mining area based on fuzzy set theory. Issue 2 (4th March 2018) - Li, Zhiqiang; Zhou, Binghua; Teng, Debin; Yang, Weimin; Qiu, Daohong
Abstract: Disordered mining activities have significantly affected the eco-geological environment of groundwater in mining area. Based on the fuzzy set theory, this paper considered three factors: the quantity of groundwater resources, groundwater environmental quality and groundwater vulnerability, and established a multi-index and multi-parameter non-linear evaluation system to make a comprehensive evaluation of the groundwater environment in the mining area. The results showed that the groundwater eco-geological environmental issues in this region were serious. The distribution area of poor quality of groundwater environment was very large, accounting for 72.5% of the studied area, and it mainly distributed in the middle and southern regions. The areas with general groundwater quality covered about 19.0% and mainly distributed in the central and northern parts in a strip shape. The areas with good groundwater quality covered about 8.5% and distributed sporadically. Moreover, in the study area, because the groundwater vulnerability was at a high level and the groundwater environmental quality was poor, the groundwater was extremely susceptible to contamination. Therefore, the groundwater environment in the area should be significantly protected during coal mining. In addition, the predicted results can provide a scientific reference for the planning and sustainable development of large coalfields.